Development of camansi flour (Artocarpus camansi Blanco) - Yap, Yvonne Marie T.
A procedure for kamansi flour production was developed using kamansi (Attocarpus camansi, Blanco) as raw material. Sufficient blanching time of the seeds and flesh were observed at 5 minutes and 1 minute, respectively, at 100°C. Dehydration of kamansi in a cabinet drier at 160°F for 4-5 hours produced a good quality flour. The flour had a fiber content of 15% and a starch content of 6%. The kamansi flour was incorporated in the oatmeal raisin cookies at 20%, 30%, and 40% level of substitution for wheat flour. The cookies at 20% level of substitution were found to be the most acceptable.